Hydrate phase equilibrium of ternary gas mixtures containing carbon dioxide, hydrogen and propane - Babu, Ponnivalavan; Yang, Ting; Veluswamy, Hari Prakash; Kumar, Rajnish; Linga, Praveen (Journal of Chemical Thermodynamics, 2013)
Hydrate phase equilibrium of the ternary guest mixtures containing carbon dioxide, hydrogen and propane at two different compositions were determined. Addition of mole composition of 2.5% propane to the fuel gas (CO2 (40%)/H-2 (60%)) mixture reduces the hydrate formation conditions by 66% at the temperature of 278.4 K. A Clausius-Clapeyron plot for the experimental results was plotted and from the slope, the enthalpy of hydrate dissociation was calculated. The enthalpy of dissociation of the mixed hydrate formed from a ternary gas mixture containing mole composition 38.1% CO2, 59.4% H-2 and 2.5% C3H8 was found to be 110 kJ.mol(-1) and hence it was concluded that the mixed hydrate formed structure II (sII) hydrates. Whereas for the ternary gas mixture containing mole composition 80.0% CO2, 18.8% H-2, and 1.2% C3H8, the enthalpy of dissociation of the mixed hydrate was found to be 78 kJ.mol(-1) and hence we believe the mixed hydrate formed structure I (sI) hydrate. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Gas hydrates; Global warming; Phase equilibrium; Pre-combustion; Thermodynamics